Mission-Coded Map Icon Decision Aids for Play-Based Multi-Unmanned Vehicle Autonomy Delegation. (September 2017) - Bartik, Jessica; Ruff, Heath; Behymer, Kyle; Frost, Elizabeth; Calhoun, Gloria; Spriggs, Sarah; Hammack, Taleri
An extended play-based human-autonomy interface paradigm was designed to support rule-based and knowledge-based behaviors for human operators tasked with managing twelve unmanned vehicles (UVs). The present research evaluates how autonomy might provide additional decision support that helps the operator correlate new mission events with the required tasks/plays to be initiated, along with the locations each play should be initiated. Each of eight participants performed 240 trials in which they designated a location or vehicle on the map in response to mission-related event prompts in a chat window. Experimental manipulations included the presence or absence of pictorial mission-coded icons on the map, the clutter level of the map, and whether or not satellite imagery was presented on the map. Both the objective performance data and subjective ratings indicated that map designations in response to mission event prompts were significantly faster when the mission-coded icons were presented on the map. Additionally, questionnaire ratings were more favorable when the mission icons were used (e.g., higher perceived performance and less workload). Suggestions are made for follow-on research.